How are we assessing near-peer teaching in undergraduate health professional education? A systematic review. (March 2017) - Irvine, Susan; Williams, Brett; McKenna, Lisa
Abstract: Background: Near Peer teaching (NPT) is reported as an effective pedagogical approach to student learning and performance. Studies in medicine, nursing and health sciences have relied mainly on self-reports to describe its benefits, focusing on psychomotor and cognitive aspects of learning. Despite increasing research reports on peer teaching internationally, little is known about the various domains of learning used in assessment of performance and objective learning outcomes of NPT. Objective: To determine the domains of learning and assessment outcomes used in NPT in undergraduate health professional education. Methods: Quantitative systematic review was conducted in accord with the PRISMA protocol and the Joanna Briggs Institute processes. A wide literature search was conducted for the period 1990–November 2015 of fourteen databases. Grey literature was undertaken from all key research articles. Studies meeting the inclusion criteria were eligible for consideration, including measured learning outcomes of near-peer teaching in undergraduate education in nursing, medicine and health sciences. Set limitations included publications after 1990 (2015 inclusive), English language and objective learning outcomes. A quality appraisal process involving two independent reviewers was used to analyse the data. Results: Of 212 selected articles, 26 were included in the review. Terminology was confusing and found to be a barrier to the review process. Although some studies demonstrated effective learning outcomes resulting from near-peer teaching, others were inconclusive. Studies focused on cognitive and psychomotor abilities of learners with none assessing metacognition, affective behaviours or learning outcomes from quality of understanding. Conclusion: The studies reviewed focused on cognitive and psychomotor abilities of learners. Even though evidence clearly indicates that metacognition and affective behaviours have direct influence on learning and performance, indicating more research around this topic is warranted. Methodological quality of the studies and lack of theoretical frameworks underpinned by educational psychology may have contributed to inconsistencies in learning outcomes reported. Highlights: The synthesis of evidence provides a foundation for future pedagogical approaches to NPT. Affective behaviours and metacognition are not objectively assessed in NPT. Inconsistencies in learning outcomes are related to lack of theory and methodological quality. Inconsistent terminology related to NPT impacts the research process. Further research is required to assess quality of understanding in assessing performance in NPT.